Investigating best practice and effectiveness of leadership wisdom among principals of excellent secondary school Malaysia: perceptions of senior assistants - Ahmad, Abdul Razaq; Salleh, Mohamad Johdi; Awang, Mohd Mahzan; Mohamad, Nazifah Alwani (Canadian Center of Science and Education, 2013)
The aim of the current study is to investigate the practices and effectiveness of leadership wisdom among the principals of excellent secondary schools as perceived by the Senior Assistants. This research employed survey approach by using a validated questionnaire. The respondents were 417 Senior Assistants, who were randomly selected from the principals of excellent secondary schools in Malaysia. The findings showed that the Senior Assistants’ perceptions of principals’ practices of leadership wisdom were positively at higher level regarding principals’ application of their knowledge to benefit the staff as well as the whole school. Interestingly, the data show that the senior assistants’ perceptions of practice effectiveness were also higher. The implication is that all senior assistants are appropriate for their duties in excellent schools. Also the study findings would inspire the educational leaders to enhance their practices of leadership wisdom to move forward the institution in the realization of Vision 2020 as well as Malaysia Education Plan 2013-2025. Keywords: leadership wisdom, excellent school, school management, effectiveness, educational leaders